2016
DOI: 10.1155/2016/3762159
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal Community Changes Associated with Cultivation of Amazon Forest Soil with Oil Palm

Abstract: This study compared soil archaeal communities of the Amazon forest with that of an adjacent area under oil palm cultivation by 16S ribosomal RNA gene pyrosequencing. Species richness and diversity were greater in native forest soil than in the oil palm-cultivated area, and 130 OTUs (13.7%) were shared between these areas. Among the classified sequences, Thaumarchaeota were predominant in the native forest, whereas Euryarchaeota were predominant in the oil palm-cultivated area. Archaeal species diversity was 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
1
8
0
2
Order By: Relevance
“…This finding is consistent with previous studies which have found that Thaumarchaeota dominate many different environments including most aquatic and terrestrial habitats [67][68][69]. Previous studies had already reported Thaumarchaeota as the predominant archaeal phyla in the soils of tropical forests [70,71].…”
Section: Hypothesis 1 Archaeal Community Composition and Diversity Wsupporting
confidence: 93%
“…This finding is consistent with previous studies which have found that Thaumarchaeota dominate many different environments including most aquatic and terrestrial habitats [67][68][69]. Previous studies had already reported Thaumarchaeota as the predominant archaeal phyla in the soils of tropical forests [70,71].…”
Section: Hypothesis 1 Archaeal Community Composition and Diversity Wsupporting
confidence: 93%
“…However, there was amplification in only one sample (SP 2.1) ( S1 Fig ). PCR using the same conditions were also performed with DNA from bulk soil collected in the same area, around diseased plants and native forest soil, provided by Tupinambá et al [ 32 ], but no amplification occurred ( S2 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the works related to palm trees focus on fruits, seeds, roots and bulk soil since these are economically important to agroindustry [ 45 ]. Tupinambá et al [ 32 ], however, used pyrosequencing to study archaeal communities in Amazon forest soil cultivated with oil palm trees. In addition, most of the studies that evaluate microorganisms associated with palm trees describe the isolation of fungi recovered from unhealthy plants by classical microbiology techniques, in an attempt to find the causal agent of palm tree diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a greater abundance of Euryarchaeota (Thermoplasmata, 21%) was detected in the former, while Thaumarchaeota (Soil Crenarchaeotic Group, 26%) relative abundance was greater in the native sites [113]. There was a separation of OTUs between the two sites, corresponding to either I.1b or I.1c thaumarchaeotic groups, with the remaining clusters affiliated to MCG.…”
Section: Archaea In Soilsmentioning
confidence: 99%
“…The authors suggested that this differentiation could be due to the addition of N fertilizers in the oil palm field, leading to an increased abundance of Candidatus Nitrosotalea. The detection of those AOA in both sites was discussed to be related to the acidic pH in those soils [113]. …”
Section: Archaea In Soilsmentioning
confidence: 99%